45th AIAA Aerospace Sciences Meeting and Exhibit 2007
DOI: 10.2514/6.2007-627
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally Augmented Flow Structures and Time Varying Loads on Turbine Blades

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to Department of Defense, Executive Services and Communications Directorate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…[50] UAE C n standard deviation behaviors seen in Figure 6 for 0.30R are representative of those at 0.47R, 0.63R, and 0.80R. [51] At all four radial locations for the rotating blade, U ∞ values below 9 or 10 m/s were accompanied by attenuated C n standard deviation levels, which remained well below C n standard deviation levels predicted for 5 percent inflow turbulence intensity. However, modest increases in U ∞ elicited a rapid and substantial rise in UAE C n standard deviation, which peaked in the range 15 ≤ U ∞ ≤ 20 m/s.…”
Section: Axisymmetric C N Unsteadiness Amplificationmentioning
confidence: 61%
See 1 more Smart Citation
“…[50] UAE C n standard deviation behaviors seen in Figure 6 for 0.30R are representative of those at 0.47R, 0.63R, and 0.80R. [51] At all four radial locations for the rotating blade, U ∞ values below 9 or 10 m/s were accompanied by attenuated C n standard deviation levels, which remained well below C n standard deviation levels predicted for 5 percent inflow turbulence intensity. However, modest increases in U ∞ elicited a rapid and substantial rise in UAE C n standard deviation, which peaked in the range 15 ≤ U ∞ ≤ 20 m/s.…”
Section: Axisymmetric C N Unsteadiness Amplificationmentioning
confidence: 61%
“…Recent research has shown that C n standard deviation levels correlate with the chord length enveloped by the shear layer. [51] The image shown in Figure 7 is a two-dimensional section extracted from a strongly three-dimensional flow field. To gain an appreciation for the complex three-dimensional character, Figure 8 shows computed surface limiting streamlines on the suction surface of the UAE blade, for U ∞ = 15 m/s.…”
Section: Courtesy Of N Sørensen Risø National Laboratorymentioning
confidence: 99%
“…This results in massive aerodynamic loading of the slender and compliant blades, mainly in blade flapwise direction depending on the local wind vector (cf., Wind ). Local aerodynamics in the rotating system are complex and rotational lift enhancement and stall delay can play important roles . Mainly due to unsteady inflow, dynamic stall effects, that is, flow separation and reattachment behavior differing from the quasistatic phenomena, may lead to significantly changing blade loads.…”
Section: System Properties Of Offshore Wind Turbines and Resulting Loadsmentioning
confidence: 99%
“…A study conducted by Schreck (2007) showed how blade pressure measurements were performed using blade surface pressure taps and transducers mounted on the inside of a large HAWT. Since, these blades are large (compared to axial fans), enough space in the blade cavity was available to encapsulate the pressure transducers and other measuring equipment.…”
Section: Experimental Analysesmentioning
confidence: 99%